African Union law : the emergence of a sui generis legal order - Amao, Olufemi; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2019)
This book explores the emergence of African Union (AU) law as a legal order and its implications for existing order in the region. As an authoritative text on the development of AU law, the book covers such pertinent issues as legislative powers, competences, direct effect in AU law, subsidiarity, interventionism, and enforcement of laws. Olufemi Amao arguesthat there is a gradual movement from intergovernmentalism to supranationalism in the African Union legal order, and explores how this trajectory gradually and incrementally de-emphasises the discourse on nation state sovereignty; a concept that has causedmany problems in the African context. Drawing upon EU law as a comparison, the book also examines how the development of supranationalism affects crucial issues such as human rights, democratic reforms, territorial matters, tribal and religious disputes, and economic relations.As a comprehensive examination of the development of law within a union, this book will be of great interest and use to students, scholars and practitioners in international law, international relations, and African studies.
chapter 1 Introduction -- chapter 2 The development of the concepts of African law and African Union law -- chapter 3 Ascertaining the sources of African Union law: a needle in a haystack? -- chapter 4 Membership of the African Union -- chapter 5 African economic and business law: green shoots in the new economic legal order -- chapter 6 Peace, security, the rule of law and African Union law -- chapter 7 Human rights in African Union law -- chapter 8 Economic, social and cultural rights and group rights in African Union law -- chapter 9 Custom, morality and African Union law: the case of sexual orientation in Africa -- chapter 10 Enforcement of African Union law -- chapter 11 Conclusions.
Keywords: African Union; Human rights; Law -- Economic aspects -- Africa; Law -- Economic aspects; Politics and government; LAW / International; African cooperation; Human rights -- Africa; Law -- Africa -- Economic aspects; Subsidiarity; POLITICAL SCIENCE / Government / International; Africa -- Politics and government